ANG II induces apoptosis of human vascular smooth muscle via extrinsic pathway involving inhibition of Akt phosphorylation and increased FasL expression - Li, Yangxin (2005)
In addition to well-documented vascular growth-promoting effects, ANG II exerts proapoptotic effects that are poorly understood. IGF-1 is a potent survival factor for human vascular smooth muscle cells (hVSMC), and its antiapoptotic effects are mediated via the IGF-1 receptor (IGF-1R) through a signaling pathway involving phosphatidylinositol 3-kinase and Akt. We hypothesized that there would be cross talk between ANG II proapoptotic effects and IGF-1 survival effects in hVSMC. To investigate ANG II-induced apoptosis and the potential involvement of IGF-1, we exposed quiescent and nonquiescent hVSMC to ANG II. ANG II induced apoptosis only in nonquiescent cells but stimulated hypertrophy in quiescent cells. ANG II-induced apoptosis was characterized by marked inhibition of Akt phosphorylation and stimulation of membrane Fas ligand (FasL) expression, caspase-8 activation, and a reduction in soluble FasL expression. Adenovirally mediated overexpression of Akt rescued hVSMC from ANG II-induced apoptosis. IGF-1R activation increased Akt phosphorylation and soluble FasL expression, and these effects were completely blocked by coincubating hVSMC with ANG II. In conclusion, ANG II-induced apoptosis of hVSMC is characterized by marked inhibition of Akt phosphorylation and stimulation of an extrinsic cell death signaling pathway via upregulation of membrane FasL expression, caspase-8 activation, and a reduction in soluble FasL expression. Furthermore, ANG II antagonizes the antiapoptotic effect of IGF-1 by blocking its ability to increase Akt phosphorylation and soluble FasL. These findings provide novel insights into ANG II-induced apoptotic signaling and have significant implication for understanding ANG II-induced remodeling in hypertension and atherosclerosis.